The value relevance of banking sector multidimensional corporate sustainability performance - Aras, Guler; Tezcan, Nuray; Furtuna, Ozlem Kutlu (WILEY, 2018)
The purpose of this paper is to evaluate Turkish banks' multidimensional corporate sustainability performance and whether banks' sustainability efforts are value related. Both qualitative and quantitative data analysis, namely content analysis, entropy based and TOPSIS techniques, have been utilized in order to measure the sustainability performance. The Spearman rank correlation coefficient has been employed to investigate the nexus between overall sustainability performance scores of the banks and market value during the years 2013 and 2015. The results of this study are insignificant in the ongoing debate on whether Turkish banks' sustainability efforts are value related. However, a significant and positive relationship has been found between the financial sustainability performance and the market value in the long run. Additionally, a multidimensional corporate sustainability model that has the five dimensions of economic, environmental, social, governance and financial disclosures has been proposed. This paper is among the first to explore the nexus between sustainability performance and market value in Turkey.
Keywords: banking sector; content analysis; corporate sustainability performance; stakeholder engagement; sustainability reporting; TOPSIS method; Turkey; value relevance; SOCIAL-RESPONSIBILITY; FINANCIAL PERFORMANCE; MARKET; DETERMINANTS; INDICATORS; GOVERNANCE; DISCLOSURE; Business & Economics; Environmental Sciences & Ecology